Application-Oriented Design and Field Trial of the Eneramic® Power Generator. (2nd June 2015) - Reuber, Sebastian; Megel, Stefan; Jürgens, Christian; Pfeifer, Thomas; Bednarz, Marc; Wunderlich, Christian; Michaelis, Alexander
Abstract : Off-grid power generation is considered as an attractive market for fuel cells. For this reason, a compact SOFC battery hybrid system is being developed and commercialized by Fraunhofer IKTS. The 100 W hybrid system operates on commercially available LPG fuels. Different prototypes are being tested in the lab and under real-life applications while a first product version is available for industrial customers. For off-grid applications frequent start-stop cycles are expected, which are challenging for the SOFC technology. Following these requirements IKTS has consistently improved robustness of the SOFC up to now 110 start-stop cycles by quality measures and the operating procedure. The reliability of the core technology highlights the power degradation of < 0.6 % per 1, 000 h over 16, 000 h of Hotbox operation. The results of the automated laboratory and field tests will be discussed in this paper.